2011
DOI: 10.4028/www.scientific.net/msf.697-698.192
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulation of Al<sub>2</sub>O<sub>3</sub>-SiC Interface

Abstract: The interfacial energy and diffusion phenomenon of the Al2O3(012)-SiC (011) interface model are studied based on molecular dynamics. The interfacial energy increases firstly until reaches its maximum 0.459J/m2at the temperature of 1500K and then decreases. The relationship of diffusion coefficients for each kind of atoms is C>Si>O>Al. Diffusion coefficients of atoms increase at first and then decrease as the temperature goes up. This indicates the diffusion mechanism has been changed during the temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Four kinds of different grain sizes RVE models were simulated under uniaxial tension to obtain normal stress with the grain boundary energy range from 1.0 J/m 2 to 3.0 J/m 2 . The material parameters of alumina are listed in Table 1 41 …”
Section: Finite Element Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…Four kinds of different grain sizes RVE models were simulated under uniaxial tension to obtain normal stress with the grain boundary energy range from 1.0 J/m 2 to 3.0 J/m 2 . The material parameters of alumina are listed in Table 1 41 …”
Section: Finite Element Modelingmentioning
confidence: 99%
“…The material parameters of alumina are listed in Table 1. 41 Flexural strength was simulated by three-point bending using the XFEM method. As shown in Figure 2A, the mechanical parameters such as fracture energy and normal stress applied in three-point bending test model was obtained by RVEs.…”
Section: The Relationship Between Normal Stress and Bending Strengtmentioning
confidence: 99%
“…Young's modulus E (GPa) 374 37 Poisson ratio 0.22 37 Fracture energy of grain E g , N/m 2.3 37 Fracture energy of grain boundary E gb , N/m 1.0 37…”
Section: Parameter Value Parameter Valuementioning
confidence: 99%
“…Shen et al [26] used molecular dynamics methods to study the cohesion of the Cu-Fe interface performance. For the study of interfaces between ceramic materials, Zhou et al [27] studied the interfacial energy and diffusion phenomena of the Al 2 O 3 (012)-SiC(011) interfacial model using a molecular dynamics approach. The results showed that the Al 2 O 3 (012)-SiC(011) interfacial model had the highest interfacial bond strength and the strongest resistance to grain boundary crack extension at 1500 K. Therefore, it is important to study the interface of composite ceramic materials to enhance their performance.…”
Section: Introductionmentioning
confidence: 99%